A Review of Microbial Mediated Iron Nanoparticles (IONPs) and Its Biomedical Applications - Muhammad Nadeem; Rijma Khan; Nausheen Shah; Ishrat Rehman Bangash; Bilal Haider Abbasi; Christophe Hano; Chunzhao Liu; Sana Ullah; Syed Salman Hashmi; Akhtar Nadhman; Jonathan Celli (Nanomaterials, 2021)
Nanotechnology is a booming avenue in science and has a multitude of applications in health, agriculture, and industry. It exploits materials’ size at nanoscale (1–100 nm) known as nanoparticles (NPs). These nanoscale constituents are made via chemical, physical, and biological methods; however, the biological approach offers multiple benefits over the other counterparts. This method utilizes various biological resources for synthesis (microbes, plants, and others), which act as a reducing and capping agent. Among these sources, microbes provide an excellent platform for synthesis and have been recently exploited in the synthesis of various metallic NPs, in particular iron. Owing to their biocompatible nature, superparamagnetic properties, small size efficient, permeability, and absorption, they have become an integral part of biomedical research. This review focuses on microbial synthesis of iron oxide nanoparticles using various species of bacteria, fungi, and yeast. Possible applications and challenges that need to be addressed have also been discussed in the review; in particular, their antimicrobial and anticancer potentials are discussed in detail along with possible mechanisms. Moreover, some other possible biomedical applications are also highlighted. Although iron oxide nanoparticles have revolutionized biomedical research, issues such as cytotoxicity and biodegradability are still a major bottleneck in the commercialization of these nanoparticle-based products. Addressing these issues should be the topmost priority so that the biomedical industry can reap maximum benefit from iron oxide nanoparticle-based products.